2020
DOI: 10.1055/a-1192-6187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 20-min Nap after Sleep Deprivation on Brain Activity and Soccer Performance

Abstract: AbstractWe examined effects of a 20-min nap following 3 h of sleep deprivation on brain wave activity, auditory reaction time, the running-based anaerobic sprint test, leg muscle strength and the rating of perceived exertion in male college soccer players. Eleven players underwent three sleep conditions; normal sleep, sleep deprivation and 20-min nap after sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 47 publications
1
51
0
Order By: Relevance
“…The impact of napping behavior on physical performance was assessed using various sport-specific measurement tests (see Table 2 ). Nine (24.7%) studies found positive effects of napping on measures of physical performance, 42–46 , 49 , 51 , 54 , 57 five (13.5%) studies revealed no impact of napping 50 , 51 , 53 , 56 , 57 and only two (5.4%) studies revealed napping had a negative impact on performance. 27 , 56 In the nine studies reporting positive effects of napping on measures of physical performance, participants were either a) well-rested or b) sleep restricted.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The impact of napping behavior on physical performance was assessed using various sport-specific measurement tests (see Table 2 ). Nine (24.7%) studies found positive effects of napping on measures of physical performance, 42–46 , 49 , 51 , 54 , 57 five (13.5%) studies revealed no impact of napping 50 , 51 , 53 , 56 , 57 and only two (5.4%) studies revealed napping had a negative impact on performance. 27 , 56 In the nine studies reporting positive effects of napping on measures of physical performance, participants were either a) well-rested or b) sleep restricted.…”
Section: Resultsmentioning
confidence: 99%
“… 5 , 6 , 8 , 24–57 Both males and females were included in 35.1% (n = 13) of studies, 5 , 6 , 8 , 29 , 30 , 32 , 34–36 , 41 , 48 , 50 , 51 8.1% (n = 3) of studies included females exclusively, 37 , 38 , 57 and 48.6% (n = 18) studies included males only. 24–26 , 31 , 33 , 37 , 40 , 42 , 43 , 45–47 , 49 , 52–56 Three studies (8.1%) did not report sex. 27 , 28 , 44 The mean age of athletes was 23±4 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations